(untitled) (Revista de Ciências Agroveterinárias, 2022)
Maize has multiple functions and can be used for human consumption, animal feed, or in industrial processes. Grain production has made Brazil a world reference. However, few cultivars are available despite the relevance of sweet corn, especially for family farmers. This is similar to baby corn, in which sweet corn or popcorn is used for its production. In the Brazilian semi-arid region, plant and animal production are limited by water deficit in the dry season. Therefore, the production of sweet and baby corn generates income from the commercialization of the ears and roughage production with the whole-plant harvest. This research has aimed to assess the agronomic performance of five cultivars for sweet corn, baby corn, and fodder production in Agreste Meridional, a semi-arid region of Pernambuco, Brazil. Two experiments were carried out in a randomized block design with five treatments (AG 1051, Alagoano, Branquinha, São Luiz, and PV2 Viçosense) and four blocks. The 1st experiment assessed the performance of the cultivars for sweet corn and fodder yield, in which the cultivars AG 1051 and Branquinha had higher yields for ears (21.9 and 20.3 Mg ha-1) and fodder (10.7 and 10.9 Mg DM ha-1), respectively. The 2nd experiment assessed the performance of the cultivars for baby corn and fodder yield, in which the cultivars AG 1051 and PV2 Viçosense obtained the highest yield for ears (3.1 and 2.9 Mg ha-1, respectively); Branquinha had a higher yield for fodder (8.9 Mg DM ha-1). Therefore, these cultivars have desirable characteristics and can be used in intensive or extensive production.